Model Pembelajaran Project Based Learning (PjBL) dan Peningkatan Keterampilan Abad 21 Peserta Didik - Yusi Srihartini; Siti Maryam; Wildya Agna Rihma (Ikatan Dai Indonesia, 2025)
21st-century education requires students to possess critical thinking, creativity, collaboration, and communication skills. One of the relevant learning models to develop these skills is Project Based Learning (PjBL). This study aims to examine the concept of PjBL and its relevance in improving 21st-century skills based on recent literature studies. This review uses a literature analysis method by collecting data from journals, articles, and scientific books. The results of the review show that consistent implementation of PjBL can enhance students' critical thinking, creativity, communication, and collaboration skills. Challenges in implementing PjBL include teacher readiness, appropriate project design, time limitations, and the availability of learning resources. To optimize the implementation of PjBL, full support from schools is required, starting from the provision of infrastructure and teacher training to the development of flexible and contextual curricula. With proper implementation, PjBL has been proven to be one of the most effective learning approaches to holistically enhance students' 21st-century skills. This study recommends the broader integration of PjBL at various educational levels as an effective learning strategy to prepare students for global challenges.